Pengembangan Modul Digital Berbasis STEM untuk Mengembangkan Kemampuan Pemecahan Masalah - Pixyoriza, Pixyoriza; Nurhanurawati, Nurhanurawati; Rosidin, Undang (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
Problem solving is one of the most important skills for students. One way to develop students' problem-solving skills is to use a digital module designed to develop problem-solving skills, namely a STEM-based digital module that is oriented towards problem-solving skills. This study aims to produce STEM-based digital modules to develop valid, practical, and effective problem solving skills. This research is a development research using the ADDIE model. The instrument used consisted of a validation sheet filled out by experts in the field of mathematics education, a practical assessment sheet for educators and students, and a learning outcome test with problem solving questions. The quality of the developed digital module is reviewed from the aspects of validity, practicality, and effectiveness. The result is that the digital module developed is included in the valid category with an overall percentage of 88,67%, and the practicality of the digital module is seen from the response of students with a percentage of 87% and the response of educators 83.90% with a very practical category. The aspect of effectiveness based on the learning outcomes test with problem solving questions has increased in terms of the results of the pretest and posttest with an N-gain of 0.69 in the medium category. Based on the results and analysis, it can be concluded that the digital module developed is valid, practical, and effective and is suitable for students to use in learning mathematics.